Former au paysagisme d’aménagement : du DESS PARME au parcours de master PPAU, trois décennies de collaboration entre Aix-Marseille université et l’École nationale supérieure de paysage Versailles-Marseille - Jean-Noël Consalès; René Girard; Benoît Romeyer; Christian Tamisier (Projets de Paysage)
By comparing the experience of three generations of pedagogical managers, this article looks back on close to thirty years of a heritage of training courses in landscape planning organised in a collaboration between Université Aix-Marseille and the École nationale supérieure de Paysage Versailles-Marseille. These courses ranged from a postgraduate degree in landscape and urban planning in Mediterranean regions (DESS Paysage et aménagement en régions méditerranéennes, PARME) and a master’s in landscape and urban planning (Master Paysage et aménagement, P&A) to a course in landscape planning (Projet de paysage, aménagement et urbanisme, PPAU). It shows that, despite administrative vicissitudes, these courses have always defended the notions of landscape architecture, land-use planning, and municipal or inter-municipal urban planning. They are based on the multidisciplinary nature of landscape sciences to understand territorial complexity, train professionals, and provide support in the management of landscape and urban planning projects. The article establishes links between lasting and changing trends in these landscape planning courses and the evolution of their territorial context, namely that of the development of the Aix-Marseille-Provence metropolis.